Method for improving strength of activated alumina balls
In the preparation process of activated alumina balls, a combination of quick-release powder, aluminum phosphate and pore-forming agent is used for in-situ crystallization, combined with modified alumina fiber and specific roasting conditions, to solve the problem of active alumina in the existing technology. The problem of insufficient strength of alumina balls has been significantly improved in strength, wear resistance and adsorption.
Patent Information
- Application Number
- CN202411520495.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-01-24
AI Technical Summary
The prior art has limited effect in improving the strength of activated alumina spheres and cannot meet the needs of some areas with high strength requirements.
By mixing the fast -deleted powder, organic amine, aluminum phosphate, pores, and water for crystallizing treatment to form a solid -phase crystallization product, and add adhesive, aluminum aluminum fiber, molding agent to the basis of it After the water, after the rolling ball mechanism is used to prepare the active aluminum oxide ball front, it is roasted twice. The first roasting is under the air atmosphere, and the second roasting is under the HF atmosphere.
The strength, wear resistance and adsorption properties of activated alumina balls are significantly improved, which can better meet high-level application requirements.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of activated alumina balls, and in particular relates to a method for improving the strength of activated alumina balls. Background Art
[0002] Activated alumina, also known as activated bauxite, is a porous, highly dispersed solid material. Its main component is aluminum oxide (Al2O3), which has a large specific surface area and rich pore structure, which makes it widely used in petrochemical, fine chemical, biological and pharmaceutical fields. For example, in petrochemical, it can be used as a catalyst and catalyst carrier; in the pharmaceutical industry, it can be used to purify the air and remove impurities in medicines; in the field of environmental protection, it can be used for sewage treatment and air purification.
[0003] The strength of activated alumina is one of the important indicators of its physical properties, which is usually measured by multiple parameters, such as particle strength (N / particle), radial compressive strength (N / cm), etc. These parameters reflect the ability of activated alumina particles to resist damage when subjected to external forces. In practical applications, the strength of activated alumina is crucial to its performance as a catalyst carrier, adsorbent and other functional materials. High-strength activated alumina can better resist wear and breakage during operation and extend its service life while maintaining its porosity and high specific surface area, thereby maintaining excellent catalytic activity and adsorption performance. Improving the strength of activated alumina can be achieved through a variety of methods, such as optimizing the production process, adjusting the raw material ratio, and improving the molding technology. For example, during the preparation process, the strength of activated alumina balls can be significantly improved by controlling the bulk density of the raw balls and the curing conditions. In addition, adding an appropriate amount of reinforcing agent or using a special treatment process can further improve its strength. The invention in CN113461408A improves the bonding strength between pseudo-boehmite by spraying pseudo-boehmite sol, making the obtained spheres more compact and improving the falling off of pseudo-boehmite powder. At the same time, the activated alumina balls are pressurized by air pressure, so that the strength of the obtained activated alumina balls is increased by 24-35% compared with the strength of alumina balls on the ordinary market, improving the disadvantage of insufficient strength of the activated alumina balls. However, the method of improving the strength of activated alumina balls with a diameter of 1-3 mm by mixing aluminum hydroxide powder, adhesive, bicarbonate, pseudo-boehmite, cellulose molding agent and water with a binder still cannot better meet the requirements in some fields with high strength requirements.
[0004] Therefore, there is an urgent need for a method for improving the strength of activated alumina balls to better improve the strength of activated alumina. Summary of the invention
[0005] The purpose of the present invention is to provide a method for improving the strength of activated alumina balls, which can not only improve the strength of activated alumina, but also improve the wear resistance and adsorption of activated alumina.
[0006] In order to achieve the above object, the present invention provides the following technical solutions: The present invention provides a method for improving the strength of activated alumina balls, the method comprising the following steps: (1) mixing the quick-de-powder, organic amine, aluminum phosphate, pore-forming agent and water and performing a crystallization treatment, filtering after the crystallization treatment, and washing the solid until the filtrate is neutral to obtain a solid phase crystallization product; (2) adding a binder, modified alumina fiber, a molding agent and water to the solid phase crystallization product, and then preparing an activated alumina ball precursor in a rolling ball forming machine; (3) calcining the activated alumina ball precursor to obtain; The pore former is selected from an organic pore former and an inorganic pore former; the calcination is divided into a first calcination followed by a second calcination, the first calcination is carried out in an air atmosphere, and the second calcination is carried out in an HF atmosphere.
[0007] In order to increase the strength of activated alumina, the existing process often uses quick-de-powder and other powders (such as molecular sieves) to directly mix them into balls under the action of a binder, and then calcine them at high temperature to obtain activated alumina. However, this method has limited effect on the increase in the strength of activated alumina. The present application uses quick-de-powder, aluminum phosphate and silica sol to directly crystallize in situ to form alumina, which is then mixed with other additives to form an activated alumina ball precursor, and then the activated alumina ball precursor is calcined. Compared with the existing process, the strength of the activated alumina balls can be better improved. The reasons are speculated to be: aluminum phosphate is crystallized in situ, quick-de-powder can participate in the crystallization, and the alumina component formed by calcination can better bond with the quick-de-powder, thereby better improving the strength of the activated alumina balls. On the other hand, the present invention has found that if aluminum phosphate is replaced with pseudo-boehmite, the improvement in the strength of the activated alumina is not as good as adding aluminum phosphate. This may be because phosphoric acid can reduce the initial grain size of alumina during the crystallization and calcination process, thereby improving its stability.
[0008] Quick-release powder is a kind of aluminum oxide powder obtained by rapid dehydration of aluminum hydroxide through suspended roasting and rapid cooling. Quick-release powder has strong activity and water absorption performance due to its high specific surface area (generally above 240 square meters / gram). Furthermore, the average particle size of the quick-release powder is 3-5 microns.
[0009] The quick-release powder in the present invention can be obtained commercially, preferably purchased from Zibo Yinghe Chemical Co., Ltd.
[0010] Furthermore, the organic amine is selected from at least one of diethylamine, ethylenediamine, triethylamine, tetramethylammonium hydroxide and tetraethylammonium hydroxide, preferably tetramethylammonium hydroxide.
[0011] The present invention has been found that organic amines and pore formers are used to control the pore structure of activated alumina. Furthermore, the weight ratio of the organic pore former to the inorganic pore former is 1:(1-5), for example, 1:1, 1:2, 1:2.5, 1:3, 1:4, 1:5, preferably 1:(2.5-3).
[0012] The use of organic pore formers and inorganic pore formers in the present invention can better balance the strength and adsorption performance of activated alumina balls. In experiments, it is found that the adsorption performance of activated alumina obtained by using organic pore formers alone is better than that of activated alumina obtained by using inorganic pore formers alone, but the strength of activated alumina is not good. Adding a specific amount of inorganic pore formers to work together with the organic pore formers can not only better increase the adsorption of activated alumina, but also reduce the impact on the strength of activated alumina balls. This may be because during the roasting process, the organic pore former decomposes at high temperature to form specific pores in the activated alumina. A single organic pore former may cause cracks to form on the surface of the activated alumina. The addition of a specific amount of inorganic pore former can synergistically play a pore-forming role with the organic pore former to prevent the occurrence of surface cracks.
[0013] Furthermore, the inorganic pore forming agent is selected from at least one of coal powder, carbon powder and silicon nitride, preferably silicon nitride. The above preferred implementation can better increase the adsorption, strength and wear resistance of activated alumina.
[0014] Furthermore, the average mesh size of the silicon nitride is 200-500 meshes, preferably 300 meshes.
[0015] The silicon nitride in the present invention can be obtained commercially, and preferably the silicon nitride is purchased from Qinghe Chaotai Metal Materials Co., Ltd., and the average mesh size is 300 meshes.
[0016] Furthermore, the organic pore-forming agent is selected from at least one of microcrystalline cellulose, hydroxyethyl methylcellulose and hydroxypropyl methylcellulose, preferably hydroxypropyl methylcellulose.
[0017] Furthermore, the water-soluble viscosity of the hydroxypropyl methylcellulose at 25° C. is 100,000-300,000 mPa.s, preferably 200,000 mPa.s.
[0018] The hydroxypropyl methylcellulose in the present invention can be obtained commercially, preferably purchased from Jinzhou Xincheng Cellulose Co., Ltd.
[0019] Furthermore, in step (1), the weight ratio of the quick-release powder to aluminum phosphate is 1:(0.5-1), for example, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, preferably 1:(0.6-0.7).
[0020] Furthermore, in step (1), the weight ratio of the aluminum phosphate to the organic amine is 1:(0.2-0.6), for example, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, preferably 1:(0.3-0.4).
[0021] Furthermore, in step (1), the weight ratio of the aluminum phosphate to the pore-forming agent is 1:(0.2-0.6), for example, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, preferably 1:(0.3-0.4).
[0022] Furthermore, in step (1), the weight ratio of the quick-release powder to water is 1:(30-100), for example, 1:30, 1:40, 1:50, 1:60, 1:70, 1:80, 1:90, 1:100, preferably 1:(50-60).
[0023] Furthermore, the conditions of the crystallization treatment include: temperature of 80-160° C., time of 8-28 h, preferably temperature of 110-120° C., time of 10-14 h.
[0024] Those skilled in the art will appreciate that the crystallization process is carried out in a closed reactor.
[0025] Furthermore, the binder is selected from at least one of an aqueous solution of ammonium bicarbonate, an aqueous solution of sodium carbonate, an aqueous solution of hydrochloric acid, an aqueous solution of nitric acid and an aqueous solution of sulfuric acid, preferably an aqueous solution of ammonium bicarbonate.
[0026] Furthermore, the mass fraction of the solute in the binder is 0.1-2%, preferably 0.5-1%.
[0027] Furthermore, the preparation method of the modified alumina fiber includes: the preparation method of the modified alumina fiber includes: calcining alumina fiber in a mixed gas of nitrogen and HF gas to obtain the modified alumina fiber.
[0028] Furthermore, when preparing the modified alumina fiber, the average mesh size of the alumina fiber is 1000-3000 mesh, preferably 2000 mesh.
[0029] The alumina fiber in the present invention can be obtained commercially, for example, from Qinghe County Chaotai Metal Materials Co., Ltd., and its average mesh number is 2000 meshes.
[0030] Furthermore, when preparing the modified alumina fiber, the concentration of the nitric acid aqueous solution is 3-4 mol / L.
[0031] Furthermore, when preparing the modified alumina fiber, the volume content of HF gas in the mixed gas is 5-10%.
[0032] Furthermore, when preparing the modified alumina fiber, the gas hourly space velocity of the mixed gas is 400-500h -1 , temperature is 400-500℃, time is 1-2h.
[0033] Those skilled in the art will appreciate that the preparation of the modified alumina fibers may be carried out in a conventional fixed bed reactor in the art, and the present invention will not elaborate on this.
[0034] During the research process, it was found that although the in-situ introduction of aluminum phosphate to form specific alumina in the present invention can better increase the strength of activated alumina, the wear resistance of the final activated alumina is significantly reduced. The present invention unexpectedly found in the research that the use of the modified alumina fiber in the present invention can increase the wear resistance and strength of the final activated alumina to a certain extent. This may be because the alumina fiber treated with nitric acid has more stable pore walls and ends. When the activated alumina is subjected to external friction, the activated alumina present in the activated alumina system can, on the one hand, play a lubricating role in the friction process, reduce the amount of wear, and enhance the wear stability. On the other hand, the external friction force is transferred to the modified alumina fiber, and the modified alumina fiber has more stable pore walls and ends, and has better anti-friction force, thereby ultimately improving the wear resistance and strength of the activated alumina.
[0035] The molding agent is selected from sesbania powder and / or kaolin, preferably sesbania powder.
[0036] Furthermore, in step (2), the weight ratio of the solid phase crystallization product to the binder is 1:(15-30), for example, 1:15, 1:18, 1:20, 1:25, 1:28, 1:30, preferably 1:(20-25).
[0037] Furthermore, in step (2), the weight ratio of the solid phase crystallization product to the modified alumina fiber is 1:(0.1-0.5), for example, 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5, preferably 1:(0.2-0.3).
[0038] Furthermore, in step (2), the weight ratio of the solid phase crystallization product to the forming agent is 1:(0.02-0.05), for example, 1:0.02, 1:0.03, 1:0.04, 1:0.05, preferably 1:(0.03-0.04).
[0039] Furthermore, in step (2), the weight ratio of the solid phase crystallization product to water is 1:(0.05-0.08), for example, 1:0.05, 1:0.06, 1:0.07, 1:0.08, preferably 1:(0.06-0.07).
[0040] Furthermore, the mixing conditions in step (2) include: a stirring speed of 800-1200 r / min and a time of 5-10 min.
[0041] Furthermore, in step (2), the particle size of the activated alumina sphere precursor is 3-5 mm.
[0042] In the present invention, the first calcination is carried out in an air atmosphere and the second calcination is carried out in an HF atmosphere, which can better increase the adsorption of the activated alumina balls.
[0043] Furthermore, the first calcination conditions include: calcination at 600-800° C. for 2-4 hours in an air atmosphere.
[0044] Furthermore, the second calcination conditions include: calcining at 400-500° C. for 1-2 hours in HF atmosphere.
[0045] Compared with the prior art, the advantages and beneficial effects of the present invention are: The method of the present invention not only significantly improves the strength of activated alumina, but also significantly improves its wear resistance and adsorption. The activated alumina finally obtained can meet higher-level application requirements. It is speculated that this is because the in-situ crystallization and rapid de-powdering of aluminum phosphate in the present invention can participate in the crystallization so that the various components in the system can be more stably combined. At the same time, the modified alumina fibers, pore-forming agents and other components and the specific calcination conditions significantly improve the strength, wear resistance and adsorption of activated alumina. DETAILED DESCRIPTION
[0046] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0047] Example 1 This embodiment provides a method for improving the strength of activated alumina balls, the method comprising the following steps: (1) After mixing the quick-de-powder, organic amine, aluminum phosphate, pore-forming agent and water, a crystallization treatment is performed at a temperature of 115° C. for 12 hours. After the crystallization treatment, the solid is filtered and washed until the filtrate is neutral to obtain a solid phase crystallization product; (2) adding a binder, modified alumina fiber, a molding agent and water to the solid phase crystallization product, and then preparing an activated alumina ball precursor in a rolling ball forming machine; (3) calcining the activated alumina sphere precursor to obtain; The quick-release powder was purchased from Zibo Yinghe Chemical Co., Ltd. The average particle size of the quick-release powder was 4 μm; The organic amine is tetramethylammonium hydroxide; The pore former is selected from a combination of an organic pore former and an inorganic pore former, with a weight ratio of 1:2.8, the organic pore former is hydroxypropyl methylcellulose (with a water-soluble viscosity of 200,000 mPa.s at 25°C, purchased from Jinzhou Xincheng Cellulose Co., Ltd.), and the inorganic pore former is silicon nitride (purchased from Qinghe Chaotai Metal Materials Co., Ltd., with an average mesh size of 300 meshes); In step (1), the weight ratio of the quick-release powder to aluminum phosphate is 1:0.65; the weight ratio of aluminum phosphate to organic amine is 1:0.32; the weight ratio of aluminum phosphate to pore-forming agent is 1:0.38; the weight ratio of the quick-release powder to water is 1:56; The binder is an aqueous solution of ammonium bicarbonate, with a mass fraction of 0.8%; The preparation method of the modified alumina fiber comprises: calcining the alumina fiber in a mixed gas of nitrogen and HF gas to obtain the modified alumina fiber; When preparing the modified alumina fiber: the alumina fiber was purchased from Qinghe Chaotai Metal Materials Co., Ltd., and the average mesh size was 2000 mesh; the volume content of HF gas in the mixed gas was 8%; the calcination conditions included that the gas hourly space velocity of the mixed gas was 460h -1 , temperature is 420℃, time is 1.5h; The molding agent is sesbania powder; In step (2), the weight ratio of the solid phase crystallization product to the binder is 1:23; the weight ratio of the solid phase crystallization product to the modified alumina fiber is 1:0.23; the weight ratio of the solid phase crystallization product to the forming agent is 1:0.03; the weight ratio of the solid phase crystallization product to water is 1:0.07; the mixing conditions include: the stirring speed is 1000r / min, the time is 8min; the particle size of the activated alumina ball precursor is 3-5mm; In step (3), the calcination is divided into a first calcination followed by a second calcination; the conditions for the first calcination include: calcination at 720°C for 3 hours in an air atmosphere; the conditions for the second calcination include: calcination at 450°C for 1.5 hours in an HF atmosphere.
[0048] Example 2 This embodiment provides a method for improving the strength of activated alumina balls, the method comprising the following steps: (1) After mixing the quick-de-powder, organic amine, aluminum phosphate, pore-forming agent and water, the mixture is crystallized at a temperature of 120° C. for 8 h. After the crystallization, the mixture is filtered and the solid is washed until the filtrate is neutral to obtain a solid phase crystallization product; (2) adding a binder, modified alumina fiber, a molding agent and water to the solid phase crystallization product, and then preparing an activated alumina ball precursor in a rolling ball forming machine; (3) calcining the activated alumina sphere precursor to obtain; The quick-release powder was purchased from Zibo Yinghe Chemical Co., Ltd. The average particle size of the quick-release powder was 4 μm; The organic amine is tetramethylammonium hydroxide; The pore former is selected from a combination of an organic pore former and an inorganic pore former, with a weight ratio of 1:2, the organic pore former is hydroxypropyl methylcellulose (the water-soluble viscosity at 25°C is 200,000 mPa.s, purchased from Jinzhou Xincheng Cellulose Co., Ltd.), and the inorganic pore former is silicon nitride (purchased from Qinghe Chaotai Metal Materials Co., Ltd., with an average mesh size of 300 meshes); In step (1), the weight ratio of the quick-release powder to aluminum phosphate is 1:0.5; the weight ratio of aluminum phosphate to the organic amine is 1:0.3; the weight ratio of aluminum phosphate to the pore-forming agent is 1:0.4; the weight ratio of the quick-release powder to water is 1:60; The binder is an aqueous solution of ammonium bicarbonate, with a mass fraction of 0.8%; The preparation method of the modified alumina fiber comprises: calcining the alumina fiber in a mixed gas of nitrogen and HF gas to obtain the modified alumina fiber; When preparing the modified alumina fiber: the alumina fiber was purchased from Qinghe Chaotai Metal Materials Co., Ltd., and the average mesh size was 2000 mesh; the volume content of HF gas in the mixed gas was 5%; the calcination conditions included that the gas hourly space velocity of the mixed gas was 420h -1 , temperature is 480℃, time is 1h; The molding agent is sesbania powder; In step (2), the weight ratio of the solid phase crystallization product to the binder is 1:20; the weight ratio of the solid phase crystallization product to the modified alumina fiber is 1:0.2; the weight ratio of the solid phase crystallization product to the forming agent is 1:0.02; the weight ratio of the solid phase crystallization product to water is 1:0.08; the mixing conditions include: the stirring speed is 1000r / min, the time is 8min; the particle size of the activated alumina sphere precursor is 3-5mm; In step (3), the calcination is divided into a first calcination followed by a second calcination; the conditions for the first calcination include: calcination at 720°C for 3 hours in an air atmosphere; the conditions for the second calcination include: calcination at 450°C for 1.5 hours in an HF atmosphere.
[0049] Comparative Example 1 The difference between this comparative example and Example 1 is that aluminum phosphate is replaced by pseudo-boehmite.
[0050] Comparative Example 2 The difference between this comparative example and Example 1 is that there is no pore-forming agent.
[0051] Comparative Example 3 The difference between this comparative example and Example 1 is that the pore-forming agent is an organic pore-forming agent (hydroxypropyl methylcellulose).
[0052] Comparative Example 4 The difference between this comparative example and Example 1 is that the pore-forming agent is an inorganic pore-forming agent (silicon nitride).
[0053] Comparative Example 5 The difference between this comparative example and Example 1 is that the modified alumina fiber is replaced by alumina fiber (ie, the alumina fiber is not modified).
[0054] Comparative Example 6 The difference between this comparative example and Example 1 is that there is no modified alumina fiber.
[0055] Comparative Example 7 The difference between this comparative example and Example 1 is that in step (3), the calcination conditions include: calcination at 720° C. for 3.5 h in an air atmosphere.
[0056] Performance Testing The activated alumina obtained in the embodiment and the comparative example were tested respectively with reference to HG∕T 3927-2020.
[0057] The test results are shown in Table 1 It can be seen from the above performance test results that the methods in Examples 1-2 significantly improve the strength, wear resistance and adsorption of activated alumina, especially the comprehensive performance of Example 1 is the most outstanding. It is speculated that this is because the in-situ crystallization and rapid de-powdering of aluminum phosphate in the present invention can participate in the crystallization, allowing the various components in the system to be more stably combined. At the same time, the modified alumina fibers, pore-forming agents and other components as well as the specific calcination conditions significantly improve the strength, wear resistance and adsorption of activated alumina.
[0058] However, the comparative example does not adopt the necessary technical solution, resulting in that it is significantly inferior to the embodiment in the corresponding performance test.
[0059] In Comparative Example 1, the aluminum phosphate in the present invention is replaced with pseudo-boehmite, and the strength of the final activated alumina is reduced, indicating that the strength of the activated alumina finally obtained by the quick de-powdering and in-situ crystallization of aluminum phosphate in the present invention is better; in Comparative Example 2, no pore former is used, and the adsorption performance of the final activated alumina is significantly reduced; in Comparative Example 3, the pore former only contains an organic pore former, and the compressive strength of the final activated alumina is significantly reduced, but the activated alumina has good adsorption, but the adsorption performance is not as good as the activated alumina obtained by containing both organic and inorganic pore formers; in Comparative Example 4, the pore former only contains an inorganic pore former, and the strength of the final activated alumina does not change significantly, and the activated alumina has good adsorption, but the adsorption performance is not as good as the activity obtained by containing both organic and inorganic pore formers; Comparative Examples 2-4 illustrate that the addition of the pore former in the present invention can increase the adsorption of the activated alumina, especially the simultaneous use of organic and inorganic pore formers can not only overcome the defect of reduced strength caused by the organic pore former, but also It can better increase the adsorption capacity of activated alumina; in comparative example 5, the alumina fiber is not modified and used, the wear resistance of the activated alumina is significantly reduced, and the strength is reduced to a certain extent; in comparative example 6, the wear resistance and strength of the activated alumina obtained without using modified alumina fiber are significantly reduced, and the strength is reduced more than that in comparative example 4; it can be seen from comparative examples 5-6 that the alumina fiber in the present invention, especially the modified alumina fiber, can better increase the wear resistance and strength of the activated alumina; in comparative example 7, it is not calcined in HF atmosphere, and the adsorption performance of the activated alumina finally obtained is reduced, indicating that calcining in HF atmosphere after calcining in air in the present invention can increase the adsorption capacity of the activated alumina.
[0060] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for improving the strength of activated alumina balls, characterized in that: The method comprises the following steps: (1) mixing the quick-de-powder, organic amine, aluminum phosphate, pore-forming agent and water and performing a crystallization treatment, filtering after the crystallization treatment, and washing the solid until the filtrate is neutral to obtain a solid phase crystallization product; (2) adding a binder, modified alumina fiber, a molding agent and water to the solid phase crystallization product, and then preparing an activated alumina ball precursor in a rolling ball forming machine; (3) calcining the activated alumina sphere precursor to obtain; The pore former is selected from an organic pore former and an inorganic pore former; the calcination is divided into a first calcination followed by a second calcination, the first calcination is carried out in an air atmosphere, and the second calcination is carried out in an HF atmosphere.
2. The method according to claim 1, characterized in that The organic amine is selected from at least one of diethylamine, ethylenediamine, triethylamine, tetramethylammonium hydroxide and tetraethylammonium hydroxide.
3. The method according to claim 1, characterized in that The inorganic pore former is selected from at least one of coal powder, carbon powder and silicon nitride.
4. The method according to claim 1, characterized in that: The organic pore former is selected from at least one of microcrystalline cellulose, hydroxyethyl methyl cellulose and hydroxypropyl methyl cellulose.
5. The method according to claim 1, characterized in that In step (1), the weight ratio of the quick-release powder to aluminum phosphate is 1:(0.5-1); the weight ratio of the aluminum phosphate to the organic amine is 1:(0.2-0.6); the weight ratio of the aluminum phosphate to the pore-forming agent is 1:(0.2-0.6); the weight ratio of the quick-release powder to water is 1:(30-100); the conditions of the crystallization treatment include: temperature of 80-160°C and time of 8-28h.
6. The method according to claim 1, characterized in that The binder is selected from at least one of an aqueous solution of ammonium bicarbonate, an aqueous solution of sodium carbonate, an aqueous solution of hydrochloric acid, an aqueous solution of nitric acid and an aqueous solution of sulfuric acid.
7. The method according to claim 1, characterized in that The preparation method of the modified alumina fiber comprises: calcining the alumina fiber in a mixed gas of nitrogen and HF gas to obtain the modified alumina fiber.
8. The method according to claim 7, characterized in that The volume content of HF gas in the mixed gas is 5-10%; the calcination conditions include that the gas hourly space velocity of the mixed gas is 400-500h -1 , temperature is 400-500℃, time is 1-2h.
9. The method according to claim 1, characterized in that: In step (2): the weight ratio of the solid phase crystallization product to the binder is 1:(15-30); the weight ratio of the solid phase crystallization product to the modified alumina fiber is 1:(0.1-0.5); the weight ratio of the solid phase crystallization product to the forming agent is 1:(0.02-0.05); the weight ratio of the solid phase crystallization product to water is 1:(0.05-0.08).
10. The method according to any one of claims 1 to 9, characterized in that: The first calcination conditions include: calcination at 600-800° C. for 2-4 hours in an air atmosphere; the second calcination conditions include: calcination at 400-500° C. for 1-2 hours in an HF atmosphere.
Citation Information
Patent Citations
Alumina ball with macroporous structure and preparation method thereof
CN110526687A
Method for improving strength of activated alumina balls
CN113461408A
Porous aluminum oxide
DE102012206665A1
Manufacturing method of alumina abrasive grains and alumina abrasive grains manufactured by the method
KR101208896B1
Ceramic precursor having improved manufacturability
US20100029462A1